Implikasi Pendirian Perseroan Perorangan Menurut Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Ditinjau dari Prinsip-Prinsip Hukum Perseroan dalam Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas - Azkiya Kamila Rosadi; Ratna Januarita (UNISBA Press, 2022)
With the enactment of Job Creation Law, the definition of a Limited Liability Company is broadened, namely a company that meets the criteria for Micro and Small Enterprises. With the categorization of micro and small enterprises into the form of LLC, there are changes in the regulation of the establishment of LLC in general, namely related to the simplification of the stages of establishing LLC as a legal entity and relaxation of the authorized capital of LLC. However, the simplification of establishment has a potential to create juridical problems. Based on this phenomenon, the problems in this research are formulated as follows: (1) How is the establishment of an MSE according to the Job Creation Law related to the Law Number 40 of 2007? and (2) What are the implications of the establishment of a MSE under the Job Creation Law on the LLC Principles in the Law Number 40 of 2007? This researcher uses normative juridical research methods using descriptive analysis research specifications, the research phase used is library research, data sources and data collection techniques used through library research using secondary data sources consisting of primary, secondary, and tertiary legal materials, and data analysis method used method of systematic interpretation and extensive interpretation. The results of this study are the establishment of an individual company has not fulfilled the elements of a legal entity and is not in accordance with the theories of legal entities that have been put forward by previous experts so that the legality of an individual company will be doubted considering that it was founded by 1 founder and is very vulnerable to conflicts of personal interest. and the mixing of company assets with personal assets as well as the loss of authorized capital in the establishment makes it difficult for individual companies to obtain capital from outside parties in large amounts due to the absence of capital guarantees as a means of paying off creditors' receivables. Dengan diundangkannya UU Cipta Kerja memperluas pengertian Perseroan Terbatas yaitu perseroan yang memenuhi kriteria Usaha Mikro dan Kecil. Dengan dikategorikannya perseroan perorangan mikro kecil kedalam bentuk PT maka terdapat perubahan dalam pengaturan pendirian PT secara umum, yakni terkait simplifikasi tahapan pendirian PT sebagai badan hukum dan relaksasi modal dasar PT. Hal tersebut namum menyimpan potensi permasalahan yuridis. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut : (1) Bagaimana pendirian Perseroan Perorangan menurut UU Cipta Kerja dikaitkan dengan UUPT? dan (2) Bagaimana implikasi pendirian Perseroan Perorangan menurut Undang-UU Cipta Kerja terhadap Prinsip-prinsip Perseroan Terbatas dalam UUPT? Peneliti ini menggunakan metode penelitian yuridis normatif dengan menggunakan spesifikasi penelitian deskriptif analisis, tahap penelitian yang digunakan studi kepustakaan, sumber data dan teknik pengumpulan data yang digunakan melalui studi kepustakaan dengan menggunakan sumber data sekunder yang terdiri dari bahan hukum primer, sekunder, dan tersier, serta metode analisis data yang digunakan metode penafsiran sistematis dan penafsiran ekstensif. Hasil dari penelitian ini adalah pendirian perseroan perorangan belum memenuhi unsur-unsur badan hukum dan kurang sesuai dengan teori-teori badan hukum yang telah dikemukakan oleh para ahli sebelumnya sehingga legalitas dari perseroan perorangan akan diragukan mengingat didirikan oleh 1 orang pendiri sangat rentan terjadinya konflik kepentingan pribadi dan percampuran harta kekayaan perseroan dengan harta kekayaan pribadi serta hilangnya modal dasar dalam pendirian mengakibatkan perseroan perorangan sulit mendapatkan modal dari pihak luar dalam jumlah yang besar dikarenakan tidak adanya jaminan modal sebagai sarana kepentingan pelunasan piutang kreditur.